Case-based approach in differentiating the choice of filling material when obturation system of root canals: the concept, sealers, strategy (Эндодонтия Today)
Based on evidence-based medicine, doctor-dentist can make the right decision on the choice of methods and means for performance of medical manipulations. Knowledge of the nature and duration of the violations of adaptive-compensatory reactions of the periodontal depending on the physico-chemical properties of sealers is an important part of endodontic treatment. In this work the problem of choice of filling material when obturation system of root canals. The results of the research could justify a differentiated approach to the choice of the root filling material with the position of evidence based medicine.